Arginase-II Deficiency Extends Lifespan in Mice - Xiong, Yuyan; Yepuri, Gautham; Montani, Jean-Pierre; Ming, Xiu-Fen; Yang, Zhihong (Frontiers in Physiology, 2017)
The mitochondrial arginase type II (Arg-II) has been shown to interact with ribosomal protein S6 kinase 1 (S6K1) and mitochondrial p66Shc and to promote cell senescence, apoptosis and inflammation under pathological conditions. However, the impact of Arg-II on organismal lifespan is not known. In this study, we demonstrate a significant lifespan extension in mice with Arg-II gene deficiency (Arg-II-/-) as compared to wild type (WT) control animals. This effect is more pronounced in the females than in the males. The gender difference is associated with higher Arg-II expression levels in the females than in the males in skin and heart at both young and old age. Ablation of Arg-II gene significantly reduces the aging marker p16INK4a levels in these tissues of old female mice, whereas in the male mice this effect of Arg-II deficiency is weaker. In line with this observation, age-associated increases in S6K1 signaling and p66Shc levels in heart are significantly attenuated in the female Arg-II-/- mice. In the male mice, only p66Shc but not S6K1 signaling is reduced. In summary, our study demonstrates that Arg-II may play an important role in the acceleration of aging in mice. Genetic disruption of Arg-II in mouse extends lifespan predominantly in females, which relates to inhibition of S6K1, p66Shc, and p16INK4a. Thus, Arg-II may represent a promising target to decelerate aging process and extend lifespan as well as to treat age-related diseases.